2014
DOI: 10.1007/s00535-014-0958-7
|View full text |Cite
|
Sign up to set email alerts
|

The human gastrointestinal tract-specific transcriptome and proteome as defined by RNA sequencing and antibody-based profiling

Abstract: We have applied a genome-wide analysis based on transcriptomics and antibody-based protein profiling to identify genes that are expressed in a specific manner within the human GIT. These genes and proteins constitute important starting points for an improved understanding of the normal function and the different states of disease associated with the GIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 50 publications
2
47
1
1
Order By: Relevance
“…The tissues with the most mRNAs highly enriched (at least 5× the levels in all other tissues) are testis (999) and brain (318). Several tissue-specific HPA publications have been published, and more are expected during 2015 with tissue-specific immunohistochemical and transcript evidence to guide specimen selection for further MS studies, for example, describing the brain, 18 liver, 19 testis, 20 kidney, 21 pancreas, 22 skin, 23 adipose tissue, 24 gallbladder, 25 lung, 26 gastrointestinal tract, 27 and cardiac and skeletal muscle. 28 HPA, v14, will be released in Fall 2015 along with a novel Rodent Brain Atlas comprising immunofluorescently stained whole-mouse-brain sections.…”
Section: A New Phase For the Human Protein Atlasmentioning
confidence: 99%
“…The tissues with the most mRNAs highly enriched (at least 5× the levels in all other tissues) are testis (999) and brain (318). Several tissue-specific HPA publications have been published, and more are expected during 2015 with tissue-specific immunohistochemical and transcript evidence to guide specimen selection for further MS studies, for example, describing the brain, 18 liver, 19 testis, 20 kidney, 21 pancreas, 22 skin, 23 adipose tissue, 24 gallbladder, 25 lung, 26 gastrointestinal tract, 27 and cardiac and skeletal muscle. 28 HPA, v14, will be released in Fall 2015 along with a novel Rodent Brain Atlas comprising immunofluorescently stained whole-mouse-brain sections.…”
Section: A New Phase For the Human Protein Atlasmentioning
confidence: 99%
“…NLRP6 is predominantly expressed in intestinal epithelial cells, including goblet cells (Elinav et al, 2011; Gremel et al, 2014; Wlodarska et al, 2014), where it was found to be essential for mucosal self-renewal, proliferation, and mucus secretion (Chen et al, 2011; Normand et al, 2011; Wlodarska et al, 2014). Likewise, ASC and caspase-1 are co-expressed in intestinal epithelial cells, yet no biochemical evidence of their assembly into an NLRP6 inflammasome has been demonstrated to date.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies intended to define the expression and function of NLRP6 have been performed in mouse models and very little research to date has involved human patients. Consistent with the mouse model, genome-wide analysis based on gastrointestinal transcriptomics revealed high expression of NLRP6 in the small intestine of healthy humans, 64 suggesting that NLRP6 might also have a specific role in the intestines of humans. Recently, we reported higher expression of NLRP6 in neutrophils, macrophages, and epithelial cells in the lungs obtained from pneumonia patients.…”
Section: Nlrp6 In Human Diseasesmentioning
confidence: 63%